Diabetic kidney disease and glycaemic control in Type-2 Diabetes at Primary Care in Kuantan, Pahang - Abdullah, Fa’iza; Kamaluzaman, Qamarul Azwan; A. Rahman, Nor Azlina; Md Aris, Mohd Aznan (Academy of Family Physicians of Malaysia, 2023)
Introduction: Diabetic kidney disease (DKD) is the primary cause of end-stage kidney disease, leading to renal and cardiovascular complications. Treatments achieving blood sugar levels under control can delay the progression of the disease. Objective: is study aims to determine the prevalence of DKD in selected primary care clinics in Kuantan, Pahang and its association with glycaemic control among T2DM patients. Methods: A retrospective study of 304 T2DM patients’ records, aged ≥18 years, was selected by systematic random sampling in four government health clinics in Kuantan. Statistical analysis was done in the SPSS version 26.0, using Pearson’s chi-square test and binomial logistic regression analysis. Results: Among the respondents, 50.3%, 69.1%, and 57.6% were aged ≥ 60 years (mean age of 59.1 years), Malay and female, respectively. 82.6% had diabetes ≥ 5 years (mean duration of 10.1 years). Most of them had at least two comorbidities (90.5%), including hypertension or dyslipidaemia, on oral glucose-lowering drugs only (56.9%) and were overweight (76.4%). e prevalence of diabetic kidney disease in T2D was 55.3% (95% CI = 54.8-55.9%). Multiple logistic regression showed that DKD was associated with age group ≥ 60 years old (AOR= 1.610 [1.19; 2.17]; p=0.02), uncontrolled blood pressure (AOR= 1.658 [1.27; 2.16]; p<0.001), and poor glycaemic control (AOR= 6.213 [3.30; 11.73]; p<0.001). Conclusion: More than half of T2DM patients suer from DKD. ose with poor glycaemic control have a six times higher risk of having DKD than those with good glycaemic control. A targeted educational program, early screening and monitoring, and aggressive treatment in T2D are vital to achieving an HbA1c target of less than 7% to curb the progression of DKD.